Tyrannosaurus Ralph - Evans, Nate (Andrews McMeel Publishing, 2017)
Ralph just wants to get home without being picked on by the local bully, but things go exactly the opposite--he runs into the bully, then only hours later wakes up in the body of a Tyrannosaurus rex in an alien arena, where he must do battle to save Earth from the Clobberus Crunch.